Social Comparison Sebagai Prediktor Body Dissatisfaction Pada Mahasiswa Universitas X Pengguna Instagram - Triyani, Devi; Abdillah, Rijal (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Until now, the use of social media has facilitated its users to communicate in cyberspace. Instagram is one of the most popular social media for students. Photo-based social media can increase Social Comparison related to appearance and body which can increase physical dissatisfaction in students. Several factors influence Body Dissatisfaction, one of which is Social Comparison. This study aims to determine the effect of body dissatisfaction on social comparison in Esa Unggul University students. The method used in this research is quantitative and uses cluster sampling. This research instrument uses body dissatisfaction and social comparison scales. The results of the simple linear regression test show that the regression coefficient is 1.530 and the coefficient of determination (R Square) is 0.666 with a significance of 0.000 (p <0.5) which shows the effective contribution of the two variables which is 15.30% and the rest is influenced by other variables or factors not examined in this study. The coefficient value shows a positive value, so it can be interpreted that body dissatisfaction positively affects social comparison. The suggestions for further research expand respondents, not focusing on other factors that have a greater influence on body dissatisfaction and social comparison.